Thermal conductivity and flash temperature - Reddyhoff,T; Schmidt,A; Spikes,H (Tribology Letters, 2019)
The thermal conductivity is a key property in determining the friction-induced temperature rise on the surface of sliding components. In this study, a Frequency Domain Thermoreflectance (FDTR) method is used to measure the thermal conductivity of a range of tribological materials (AISI 52100 bearing steel, silicon nitride, sapphire, tungsten carbide and zirconia). The FDTR technique is validated by comparing measurements of pure germanium and silicon with well-known values, showing discrepancies of less than 3%. For most of the tribological materials studied, the thermal conductivity values measured are reasonably consistent with values found in the literature. However the measured thermal conductivity of AISI 52100 steel (21 W/mK) is less than half the value cited in the literature (46 W/mK). Further bulk thermal conductivity measurements show that this discrepancy arises from a reduction in thermal conductivity of AISI 52100 due to through-hardening. The thermal conductivity value generally cited and used in the literature represents that of soft, annealed alloy, but through-hardened AISI 52100, which is generally employed in rolling bearings and for lubricant testing, appears to have a much lower thermal conductivity. This difference has a large effect on estimates of flash temperature and example calculations show that it increases the resulting surface temperatures by 30 to 50%. The revised value of thermal conductivity of bearing steel also has implications concerning heat transfer in transmissions.